RETROSPECTIVE ANALYSIS AND LEGAL FRAMEWORK FOR THE INTRODUCTION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE JUDICIAL SYSTEM OF UZBEKISTAN - Karomatjon Davletova (Scholar Express Journals, 2025)
This article presents reflections on the retrospective analysis and legal foundations of applying information and communication technologies in the activities of economic courts. It also discusses how this process has developed gradually, systematically, and as one of the priority areas of reform.
Keywords: Economic court; judge; information and communication technologies